THE NATION BRAND AND ITS STRATEGIC REFLECTION: Journal Special Focus: Introduction (The Strategic Review for Southern Africa, 2021)
In October 2016, the University of Pretoria, in association with Brand South Africa, hosted the first Nation Brand University Dialogue. For most participants, this was a rare opportunity to interrogate the need for a nation brand, assess the factors that shape it, examine the reciprocal effect between nation branding and the policy environment, and consider its potential limitations. From the ten presentations and extended panel discussion presented during the Dialogue, we chose to include five in this special focus because each reviewed a specific strategic aspect of nation branding.Branding as a concept is often restricted to the world of business and the marketing of products and services. But while promoting a nation's brand does rely on marketing tactics, the political scientists studying branding acknowledge that its purpose is far broader. From a strategic perspective, nation branding seeks to grow a positive predisposition towards a country's principles, policies and products, which, in turn, is used to leverage a nation's soft power authority to advocate forspecific objectives in the world's centres of power.
Keywords: University of Pretoria; Political Sciences; nation branding; policy environment; Strategic Review for Southern Africa; vol. 39 no. 1 2017; strategic refection; university dialogue; marketing tactics